Answer:
Step-by-step explanation:
Answer:
it's d it makes alot of sense and ik it's right
Answer:
dnsjsjdkdksldnd xidjdbdksksjdkdnjddj
Answer:
-2y, -2xy
Step-by-step explanation:
got it correct on the assignment :)
General form of a linear equation is ax+by+c=0 where a,b, and c are three real numbers.
So, we can shift all the terms in one side of the equation. Hence, first step is to remove y from the left side. So, subtract y from each sides.
y-y=3x+2-y
0= 3x - y +2 (By simplifying)
So, the general form of the given equation is 3x-y+2=0.